ماحولیاتی آلودگی کے اسباب اور اسلامی تعلیمات کی روشنی میں تدارک - Nouman Bashir; Dr. Syed Hamid Farooq Bukhari (الآفاق اسلامی و تحقیقی مجلہ)
The human and animal life in the present era is threatened by the enormously dangerous effects of environmental pollution. Many species are becoming extinct and the threat of pollution is multiplying day by day. Islam is a religion of nature. Islam guides humanity in their natural human needs and goals for peaceful and comfortable life in a society. Environment is one of these basic needs which provides base for the preservation of living things. The undue interference and over exploitation of natural resources (forests, water and air) are causes of environmental pollution. The root cause of this is ignorance and lack of fear of problems that they will face in future. Due to ignorance man does not know about his harmful activities to environment. One does not know what harmful effects are caused by environmental pollution and could be the causes of this pollution and what should be the remedy of this. Men puts their personal interests in the fore front for their selfishness even though they know that their deeds are harmful to other living species on this planet. If fear of God dwells in human heart, the entire humanity will not harm others for personal interests. Much has been discussed about the ecosystem and its conservation. The present paper deliberates Islamic teachings on the subject and also aimed to highlight the teachings and instructions of Islam about protection of environment. As the Muslim communities consist on a big portion of the world population, so if they adopt these principles, positive changes can be brought in global environment.